Phubbing and Learning Behaviour of Students at Budi Satrya Senior High School Medan - Harahap, Fachry Fauzy; Dora, Nuriza (FKIP - Universitas Riau, 2025)
The phenomenon of phubbing ignoring social interactions by focusing more on smartphone use is increasingly widespread among students at SMAS Budi Satrya Medan and has a significant impact on their learning behaviour. This study aims to identify the negative effects of phubbing on students’ concentration, motivation, and academic performance, as well as to explore the strategies teachers implement to address this issue. Using a qualitative descriptive approach, data were collected through observation, in depth interviews, and document analysis. The results indicate that phubbing behaviour causes serious attention diversion, disrupts the learning process, lowers student participation, and weakens social interaction in the classroom. Teachers employ various methods such as restricting smartphone use during lessons, educating students about the negative impacts of phubbing, using face-to-face communication approaches, and assigning group tasks to minimize phubbing effects. This study emphasizes the crucial role of educators in actively raising awareness and creating a conducive learning environment to reduce phubbing behaviour and support optimal academic achievement in the digital era.